Laccase immobilization on bacterial nanocellulose membranes: Antimicrobial, kinetic and stability properties. (10th July 2016) - Sampaio, Liliana M.P.; Padrão, Jorge; Faria, Jorge; Silva, João P.; Silva, Carla J.; Dourado, Fernando; Zille, Andrea
Highlights: Successful immobilization of a laccase on bacterial cellulose for wound dressings. Bacterial cellulose structure is manly formed by pure crystalline Iα cellulose. Activation energies and optimum pH of free laccase depend on the substrate employed. Entrapped laccase maintains some flexibility and accessibility of the substrate. Antimicrobial effect of immobilized laccase in Gram-positive and negative bacteria Abstract: This work studied the physical immobilization of a commercial laccase on bacterial nanocellulose (BNC) aiming to identify the laccase antibacterial properties suitable for wound dressings. Physico-chemical analysis demonstrates that the BNC structure is manly formed by pure crystalline Iα cellulose. The pH optimum and activation energy of free laccase depends on the substrate employed corresponding to pH 6, 7, 3 and 57, 22, 48 kJ mol −1 for 2, 6-dimethylphenol (DMP), catechol and 2, 2′-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), respectively. The Michaelis–Menten constant (Km) value for the immobilized laccase (0.77 mM) was found to be almost double of that of the free enzyme (0.42 mM). However, the specific activities of immobilized and free laccase are similar suggesting that the cage-like structure of BNC allows entrapped laccase to maintain some flexibility and favour substrate accessibility. The results clearly show the antimicrobial effect of laccase in Gram-positive (92%) and Gram-negative (26%) bacteria and cytotoxicity acceptable for wound dressing applications.